Pengaruh Budaya Strategis pada Kepemimpinan dan Revolusi Islam Iran - Prabaswari Prabaswari (Indonesia Center for Middle East Studies, 2021)
The Islamic Revolution in Iran, led by Ayatollah Imam Khomeini, was a world-shaking movement. Khomeini is both a spiritual leader of the ulama and a well-respected political figure in Iran. The Iran-Iraq war and US economic sanctions for reasons relating to the nuclear program have brought Khomeini's leadership model to the test. Despite these obstacles, Iran has managed to establish a constitutional government that provides the religious elite extraordinary powers so that they may control internal politics as well as external forces that threaten the regime's survival. This study finds that the Islamic Republic of Iran's achievement in building an effective government is due to Iran's ability to convert the flexible Iranian Persian and Shia Islam culture into a strategic culture. This study uses the method of analysis of the study of literature and strategic culture theory, in relation to foreign policy decision making.